Modern trends in hotel industry - Sekulić Dejan; Mandarić Marija (Ekonomski Pogledi, 2013)
The basic prerequisite for successful business of any hotel is a satisfied customer. Success in business means constant innovation in the quality of hotel products and services, that will contribute to the differentiation in the market and achieve competitive advantage. The aim of this paper is to present a global picture of the hotel industry, hotel chains and major hotel brands, market trends, innovations in hotel design and construction, the importance of information technology for business and consumer impact on the marketing strategy of hotel companies, in terms of creating new products and services. Also, the authors attempt to show the impact of modern global trends in the hotel industry in Serbia, market structure and the expected changes and trends in this area, as well as the importance of an educated managers for a successful business.